Graphene copper composite material preparation method capable of simultaneously achieving in-situ growth and hot pressed sintering

By coating a solid carbon source in the same hot-pressing chamber and subjecting it to high-temperature and high-pressure treatment, in-situ growth and hot-pressing sintering of graphene-copper composite materials are achieved, solving the problems of high cost and complex process in existing technologies, and realizing the preparation of graphene-copper composite materials with high electrical conductivity and large-scale production.

CN120921770APending Publication Date: 2025-11-11ELECTRIC POWER RES INST OF GUANGXI POWER GRID CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511024419.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing methods for preparing graphene-copper composite materials are costly, complex, and difficult to mass-produce. Furthermore, graphene is easily damaged during transfer and stacking, which affects the improvement of electrical conductivity.

Method used

In the same hot-press chamber, graphene is grown in situ and hot-pressed by coating a solid carbon source solution on the surface of copper foil and then subjected to high temperature and high pressure treatment. This combines the two steps into one, avoiding damage to the graphene during the transfer process.

Benefits of technology

The preparation of graphene-copper composite materials with high electrical conductivity has been achieved, with conductivity reaching 101~108% IACS, exceeding the international standard for annealed copper, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120921770A_ABST
    Figure CN120921770A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene copper composite material preparation method capable of achieving in-situ growth and hot pressed sintering at the same time, and relates to the technical field of metal-based composite materials. The specific preparation method comprises the following steps: coating a solid carbon source solution on the surface of pure copper foil, and drying to obtain a copper foil element; copper foil elements are stacked layer by layer in a hot-pressing cavity, gaps are reserved between the adjacent copper foil elements, and the graphene in-situ growth and hot-pressing sintering processes are achieved at the same time through high-temperature and high-pressure treatment, so that the graphene copper composite material is obtained. Different from a process flow in which graphene growth and hot pressed sintering are carried out step by step in the prior art, the process flow adopted by the method is simple, good in repeatability and beneficial to large-scale production, in-situ growth can be realized in the densification treatment process, and the method is suitable for large-scale production. Impurities and mechanical stress possibly introduced in the process of transferring the graphene copper foil among the steps are avoided, the completeness and uniformity of graphene are ensured, the interface quality of the composite material is improved, and the breakthrough of the conductivity is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composites technology, and in particular to a method for preparing graphene-copper composites that simultaneously achieves in-situ growth and hot-pressing sintering. Background Technology

[0002] Copper-based materials are widely used in energy transmission and electronic information fields due to their excellent electrical properties. Traditional methods for preparing single-crystal copper or oxygen-free copper are approaching their physical limits, making it difficult to further improve the electrical conductivity of copper-based materials. Graphene has high electron mobility, while the copper matrix has high electron concentration; the two complement each other. Graphene can serve as a highly conductive reinforcement for the copper matrix, thus promising the development of ultra-high conductivity graphene / copper composite materials with high mobility and high electron concentration.

[0003] However, there is a certain lattice mismatch between graphene and the copper matrix, and their wettability is poor. The quality of graphene on the copper foil surface is difficult to control during the growth process. This will lead to weak interfacial bonding during the subsequent densification assembly process, thereby reducing the interfacial quality and limiting the further improvement of the electrical conductivity of graphene / copper composite materials.

[0004] Currently, the preparation method of highly conductive graphene / copper-based composite materials mainly involves graphene growth followed by densification. Existing patent CN106584976A, published on April 26, 2017, discloses a highly conductive graphene / copper-based lattice composite material and its preparation method, including the following steps: 1) Graphene growth: Graphene is grown on the surface of a copper substrate using chemical vapor deposition technology to obtain graphene-copper composite units; 2) Hot-pressing sintering: Multiple graphene-copper composite units are stacked and densified by hot-pressing sintering to obtain a graphene / copper-based lattice composite material with a maximum conductivity of 117% IACS. Patent CN114953620 A, published on August 30, 2022, discloses a method for preparing graphene-copper composite materials combining hot-pressing sintering and chemical vapor deposition. In this method, multiple layers of copper foil are pre-placed in a hot-pressing chamber. Graphene is grown on the surface of the copper foil using chemical vapor deposition, followed by hot-pressing sintering to obtain a composite block, achieving a high conductivity graphene / copper composite material with a conductivity between 108% and 118% IACS. However, the aforementioned technology has the following problems: First, the use of chemical vapor deposition for graphene growth is costly and difficult to achieve large-scale production. Second, graphene growth and hot-pressing sintering of the composite unit are carried out step-by-step in different chambers, making the preparation process complex. During the transfer and stacking of the graphene-copper foil between steps, it is difficult to avoid the introduction of impurities and mechanical stress, which can easily damage the integrity of the graphene. Therefore, establishing a simple, easy-to-produce, and highly reliable method to further improve the conductivity of graphene / copper-based composite materials is of great significance. Summary of the Invention

[0005] To address the above shortcomings, this invention provides a method for preparing graphene-copper composite materials that simultaneously achieves in-situ growth and hot-pressing sintering. This method solves the problem of the difficulty in large-scale production of existing graphene-copper composite materials. The method has a simple process flow, is easy to produce, and the resulting composite material has a high conductivity of 101~108% IACS, exceeding international standards for annealed copper and meeting application requirements. The specific technical solution is as follows: A method for preparing graphene-copper composite material that simultaneously achieves in-situ growth and hot-pressing sintering, the method comprising: uniformly coating a solid carbon source solution on the surface of a pure copper foil, and obtaining a copper foil moiety with a surface carbon source coating after drying; stacking the copper foil moiety layer by layer in a hot-pressing chamber, leaving a certain gap between adjacent copper foil moiety during stacking; and performing high-temperature and high-pressure treatment to simultaneously achieve in-situ growth of graphene and hot-pressing sintering process, thereby obtaining the graphene-copper composite material.

[0006] Preferably, the original pure copper foil has a thickness of 15~25 μm and a purity of ≥99%. If the copper foil is too thin, it is prone to deformation and wrinkles, which is not conducive to the growth and pressing of graphene; if the copper foil is too thick, the graphene doping ratio is low, and the improvement in conductivity is small; while if the copper foil purity is low, impurities will affect the improvement in conductivity; if the purity is high, the production cost will also increase.

[0007] Preferably, the solid carbon source is polymethyl methacrylate (PMMA), and the solid carbon source solution is prepared by mixing PMMA with anisole solvent to form a PMMA / anisole solution with a PMMA mass fraction of 4-7 wt%. A lower PMMA concentration is detrimental to the effective growth of graphene, while a higher concentration will result in an excessively thick graphene layer on the copper foil surface, which is detrimental to conductivity.

[0008] Preferably, the coating is performed by using a pipette to transfer the solid carbon source solution onto the copper foil surface at a spin coating speed of 500~3000 r / min and a spin coating time of 30~60 s, so as to make it uniformly dispersed.

[0009] Preferably, the drying process is carried out at 80~120℃ for 1~2 hours, with the aim of curing the surface coating and removing anisole.

[0010] Preferably, the hot pressing chamber is a chamber in a rapid hot pressing sintering furnace, which includes a mold and upper and lower pressure heads.

[0011] Preferably, the distance between adjacent copper foil units stacked layer by layer in the hot pressing chamber is 0.1~1mm, specifically, the spacing between copper foil units is controlled by tooling fixtures.

[0012] Preferably, the simultaneous in-situ growth of graphene and hot-pressing sintering process refers to: simultaneously performing hot-pressing sintering in the same hot-pressing chamber to achieve in-situ growth of graphene, combining the two key steps into one. Specifically, under a hydrogen / argon atmosphere, the temperature is raised to 800~1000℃ and held for 8~10 minutes to achieve in-situ growth of graphene on the copper foil surface; simultaneously, a pressure of 10~200 MPa is applied under this environment, and the holding time is 10~30 minutes to achieve the preparation of graphene / copper-based composite blocks.

[0013] The present invention also provides a graphene-copper composite material prepared by the above method, which can simultaneously achieve in-situ growth and hot pressing sintering. This composite material can be used to prepare conductors with an electrical conductivity of 101~108% IACS.

[0014] Compared with the prior art, the beneficial effects of the present invention are: The in-situ graphene growth and hot-pressing sintering processes in this invention are carried out in the same chamber, and the two steps are combined into one. This allows for simultaneous in-situ graphene growth during densification, effectively avoiding the introduction of impurities and mechanical stress during the transfer of graphene to copper foil between steps. This ensures the integrity and uniformity of the graphene and achieves a further breakthrough in electrical conductivity. Compared with existing technologies, this invention has a simpler process flow, is easier to manufacture, and can achieve large-scale industrial production. Furthermore, the composite material obtained by this method has an electrical conductivity of 101~108% IACS, which is high, exceeding international standards for annealed copper, and meets application requirements. Attached Figure Description

[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below.

[0016] Figure 1 This is a schematic diagram of the structure of the graphene / copper-based composite material device prepared for the example.

[0017] Figure 2 The image shows a microstructure of the cross-section of the graphene / copper-based composite material block prepared in Example 1. Detailed Implementation

[0018] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.

[0019] Example 1 This embodiment includes the following steps: Step 1) Transfer a 4 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0020] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0021] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, keeping the spacing between 0.1-1mm. See the equipment diagram below. Figure 1 As shown.

[0022] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 900℃ and held for 10 min to achieve in-situ growth of graphene on the copper foil surface. A pressure of 50 MPa is applied under this environment, and the holding time is 20 min, simultaneously achieving the preparation of the graphene / copper-based composite block.

[0023] Step 5) The room temperature conductivity of the prepared composite bulk was tested using a van der Bauer conductivity measuring device. This device consists of a nanovoltmeter, a constant current source, and four probes. During the first measurement, probes 1 and 2 were energized, while probes 3 and 4 were used to measure voltage. During the second measurement, probes 2 and 3 were energized, while probes 1 and 4 were used to measure voltage. The final calculated conductivity of the graphene-copper composite bulk was 108% IACS, exceeding the international standard for annealed copper. This demonstrates that the graphene-copper based composite bulk prepared in this embodiment meets the application requirements.

[0024] The cross-sectional microstructure of the graphene / copper composite material prepared in this embodiment is shown in the image below. Figure 2 As shown, the composite material maintains a good layered structure, with flat and high-quality interfaces, which is beneficial to improving electrical conductivity.

[0025] Example 2 This embodiment includes the following steps: Step 1) Transfer a 6 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0026] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0027] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, which should be between 0.1-1mm.

[0028] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 900℃ and held for 10 min to achieve in-situ growth of graphene on the copper foil surface. A pressure of 50 MPa is applied under this environment, and the holding time is 20 min, simultaneously achieving the preparation of the graphene / copper-based composite block.

[0029] Step 5) The room temperature conductivity of the prepared composite bulk was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk was 102% IACS, exceeding the international standard for annealed copper. This indicates that the graphene-copper based composite bulk prepared in this example meets the application requirements.

[0030] Example 3 This embodiment includes the following steps: Step 1) Transfer a 4 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0031] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0032] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, which should be between 0.1-1mm.

[0033] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 1000°C and held for 10 minutes to achieve in-situ growth of graphene on the copper foil surface. The temperature is then adjusted to 900°C, a pressure of 50 MPa is applied, and the holding time is 20 minutes to simultaneously prepare the graphene / copper-based composite block.

[0034] Step 5) The room temperature conductivity of the prepared composite bulk was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk was 106% IACS, exceeding the international standard for annealed copper. This indicates that the graphene-copper based composite bulk prepared in this example meets the application requirements.

[0035] Example 4 This embodiment includes the following steps: Step 1) Transfer a 4 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0036] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0037] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, which should be between 0.1-1mm.

[0038] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 900°C and held for 10 minutes to achieve in-situ growth of graphene on the copper foil surface. The temperature is then adjusted to 800°C, a pressure of 50 MPa is applied, and the holding time is 20 minutes to simultaneously prepare the graphene / copper-based composite block.

[0039] Step 5) The room temperature conductivity of the prepared composite bulk was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk was 104% IACS, exceeding the international standard for annealed copper. This indicates that the graphene-copper based composite bulk prepared in this example meets the application requirements.

[0040] Example 5 This embodiment includes the following steps: Step 1) Transfer a 4 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0041] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0042] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, which should be between 0.1-1mm.

[0043] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 900℃ and held for 10 min to achieve in-situ growth of graphene on the copper foil surface. A pressure of 25 MPa is applied under this environment, and the holding time is 20 min, simultaneously achieving the preparation of the graphene / copper-based composite block.

[0044] Step 5) The room temperature conductivity of the prepared composite bulk was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk was 101% IACS, exceeding the international standard for annealed copper. This indicates that the graphene-copper based composite bulk prepared in this example meets the application requirements.

[0045] Comparative Example 1 This comparative example includes the following steps: Step 1) Transfer a 4 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0046] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0047] Step 3) Place multiple copper foil units into a tube furnace and raise the temperature to 900°C in a hydrogen / argon atmosphere. Hold the temperature for 10 minutes. The process parameters for this step are the same as those in the example, to achieve in-situ growth of graphene on the copper foil surface.

[0048] Step 4) Stack the in-situ grown graphene copper foil layer by layer and transfer it to a hot pressing chamber. Under an argon atmosphere, the sintering temperature is 900°C, the pressure is 50MPa, and the holding time is 20min. The process parameters for this step are the same as those in the example, thus realizing the preparation of graphene / copper-based composite blocks.

[0049] Step 5) The room temperature conductivity of the prepared composite bulk material was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk material was 98% IACS, which is lower than the international standard for annealed copper and does not meet the requirements for use.

[0050] Comparative Example 2 This embodiment includes the following steps: Step 1) Transfer an 8 wt% solid carbon source PMMA / anisole solution to the copper foil surface using a pipette. The spin coating program is to rotate at 500 r / min for 30 s, followed by 3000~4000 r / min for 1 min to ensure uniform dispersion of the coating layer.

[0051] Step 2) Place the copper foil coated with solid carbon source in a vacuum oven and dry it at 80°C for 2 hours to obtain a copper foil unit with a surface carbon source coating.

[0052] Step 3) Stack multiple copper foil units and place them in the hot pressing chamber. Use tooling fixtures to control the spacing between the copper foils, which should be between 0.1-1mm.

[0053] Step 4) Under a hydrogen / argon atmosphere, the temperature is raised to 900℃ and held for 10 min to achieve in-situ growth of graphene on the copper foil surface. A pressure of 50 MPa is applied under this environment, and the holding time is 20 min, simultaneously achieving the preparation of the graphene / copper-based composite block.

[0054] Step 5) The room temperature conductivity of the prepared composite bulk material was tested using a van der Bauer conductivity measuring device. The specific testing method was the same as in step 5 of Example 1. The final calculated conductivity of the graphene-copper composite bulk material was 95% IACS, which is lower than the international standard for annealed copper and does not meet the requirements for use.

[0055] Table 1 lists the process parameters and material properties in the above embodiments and comparative examples. The data in Table 1 for Example 1 and Comparative Example 1 (divided chambers) show that placing in-situ graphene growth and hot pressing sintering in the same chamber can avoid damage to the graphene during transfer, thereby improving the electrical conductivity of the composite material.

[0056] The data in Table 1 for each embodiment and Comparative Example 2 show that when graphene in-situ growth and hot pressing sintering are carried out in the same chamber, its electrical conductivity is affected by many factors such as carbon source concentration, growth temperature, hot pressing pressure, and hot pressing temperature. If any of these factors change, the material with electrical conductivity that meets the standard cannot be obtained. Only by using the process of the present invention can a composite material with high electrical conductivity be obtained when carried out in the same chamber.

[0057] This invention, through specific practical experiments, involves uniformly coating a solid carbon source solution onto the surface of a pure copper foil, and obtaining copper foil basic units with a surface carbon source coating after drying. The copper foil basic units are then stacked layer by layer in a hot-pressing chamber with certain gaps. After high-temperature and high-pressure treatment, graphene is grown in situ simultaneously with the hot-pressing sintering process. These two key steps are combined into one to prepare the resulting graphene / copper composite material. The conductivity of this material is tested at room temperature using a van der Bauer conductivity measurement device, and the final conductivity range is between 101 and 108% IACS, meeting the standard requirements.

[0058] In summary, compared with existing technologies, the process of this invention is simple, highly repeatable, and conducive to large-scale production. Unlike existing technologies that separate graphene growth and hot-pressing sintering, this invention simultaneously achieves in-situ graphene growth and hot-pressing sintering in the same chamber to obtain a composite material. This avoids impurities and mechanical stress that may be introduced during the transfer of graphene copper foil between steps, ensuring the integrity and uniformity of graphene, effectively improving the interface quality in graphene-copper-based composite materials, and achieving a further breakthrough in high conductivity.

[0059] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing graphene-copper composite materials that simultaneously achieves in-situ growth and hot-pressing sintering, characterized in that, The preparation method includes: uniformly coating a solid carbon source solution on the surface of a pure copper foil, and obtaining a copper foil unit with a surface carbon source coating after drying; stacking the copper foil unit layer by layer in a hot pressing chamber, leaving a certain gap between adjacent copper foil units during stacking; and performing high temperature and high pressure treatment to simultaneously achieve in-situ graphene growth and hot pressing sintering process, thereby obtaining the graphene copper composite material.

2. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The original pure copper foil has a thickness of 15~25 μm and a purity of ≥99%.

3. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The solid carbon source is polymethyl methacrylate, and the solid carbon source solution is prepared by mixing the polymethyl methacrylate with anisole solvent to form a polymethyl methacrylate / anisole solution with a mass fraction of 4-7 wt%.

4. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The coating process involves transferring the solid carbon source solution onto the copper foil surface using a pipette, with a spin coating speed of 500~3000 r / min and a spin coating time of 30~60 s.

5. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The drying process involves treating the sample at 80-120°C for 1-2 hours.

6. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The hot pressing chamber is specifically a chamber in a rapid hot pressing sintering furnace, which includes a mold and upper and lower pressing heads.

7. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The distance between adjacent copper foil units stacked layer by layer in the hot-pressing chamber is 0.1~1mm.

8. The method for preparing graphene-copper composite materials that simultaneously achieve in-situ growth and hot-pressing sintering according to claim 1, characterized in that, The process of simultaneously achieving in-situ growth of graphene and hot-pressing sintering refers to the simultaneous in-situ growth of graphene during hot-pressing sintering within the same hot-pressing chamber, combining two key steps into one. Specifically, under a hydrogen / argon atmosphere, the temperature is raised to 800~1000℃ and held for 8~10 minutes to achieve in-situ growth of graphene on the copper foil surface; simultaneously, a pressure of 10~200 MPa is applied under this environment, and the holding time is 10~30 minutes to achieve the preparation of graphene / copper-based composite blocks.

9. A graphene-copper composite material prepared by any one of the methods described in claims 1 to 8, capable of simultaneously achieving in-situ growth and hot-pressing sintering.

Citation Information

Patent Citations

  • High-conductivity graphene / copper-based layered composite material and preparation method thereof

    CN106584976A

  • Hot pressed sintering and chemical vapor deposition combined graphene copper composite material preparation method

    CN114953620A